Water Scarcity Communication in the UK: Learning From Water Company Communications Following the 2018 Heatwave - Larbey, Ruth; Weitkamp, Emma (Frontiers in Environmental Science, 2020)
When communicating about water scarcity, public water companies in the UK operate within a fine balance. There is a legal obligation on water companies in the UK to promote efficient water use, and pressure on water resources means that water companies need to encourage changes in water consumption behaviors. However, there is a lack of information about the way UK water companies communicate with the public. This paper presents the results of research into UK water company practices and perceptions in engaging consumers around water scarcity and water saving and discusses what this means for water scarcity communication. Interviews with 10 water company communication teams (14 interviewees) following the 2018 UK heatwave explored opportunities, innovations and challenges in public communication. Interviewees recognized the need for an ongoing conversation about water in the UK and identified a number of practices which could support a change in public water consumption. The results highlight the perceived importance of trust, timing and community- or group-scale communications, and the need for a cross-sectoral and intergenerational approach to public communication about water resources. This research examines some of the current underlying assumptions of water companies about what influences public water consumption in the UK and offers insights into some of the key challenges and opportunities for the future.